Fundamental rights and rights reserved for immigrant refugees: A perspective on human dignity - Filho, Claudio Xavier de Bastos; Garcia, Ana Carolina de Morais; Bezerra, Maria Marciária Martins (Seven Editora, 2023)
This research aimed to analyze the perspective of human dignity based on the theories of Jürgen Habermas and Hannah Arendt, focusing on the evolution of migration legislation in Brazil. In short, it examines the repeal of the Alien Statute and its replacement by the new Migration Law in the face of subjects not considered refugees. The study sticks to the new law in the face of the situation of Afghan refugees at Guarulhos International Airport and the case of Pacaraima-RR. The research is a bibliographic analysis in the dialectical perspective with data analysis. Thus, the research concludes that the repeal of the Alien Statute and the replacement by the new Migration Law have not been effective in protecting the human dignity of immigrants, as evidenced by the cases of Afghan refugees in Guarulhos and Pacaraima-RR. These results indicate the urgent need for more adequate policies of reception and respect for the fundamental human rights of immigrants, the results obtained indicate the violation of the founding principle of human dignity founding the Federative Republic of Brazil. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-171